2019
DOI: 10.1007/s12264-019-00343-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Single Nucleotide Polymorphisms, Cognitive Dysfunction, and Postmortem Brain Pathology in Alzheimer’s Disease Among Han Chinese

Abstract: In this study, the distribution of five Alzheimer's disease (AD)-related single nucleotide polymorphisms (SNPs) in the Han population was examined in combination with the evaluation of clinical cognition and brain pathological analysis. The associations among SNPs, clinical daily cognitive states, and postmortem neuropathological changes were analyzed in 110 human brains from the Chinese Academy of Medical Sciences/Peking Union Medical College (CAMS/PUMC) Human Brain Bank. APOE e4 (OR = 4.482, P = 0.004), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Recently, several rare mutations have been associated with late-onset AD (LOAD) in the prodomain of ADAM10, and two mutations promote amyloid pathology by diminishing α-secretase activity 40 . This year, a genome-wide association study (GWAS) identified a common variant in ADAM10 which was associated with increased AD risk 41 , which has been confirmed in Han Chinese population 42 . These findings suggest that decreased levels and activity of ADAM10 are involved in AD pathogenesis, and ADAM10 is a promising therapeutic target 43 .…”
Section: Discussionmentioning
confidence: 94%
“…Recently, several rare mutations have been associated with late-onset AD (LOAD) in the prodomain of ADAM10, and two mutations promote amyloid pathology by diminishing α-secretase activity 40 . This year, a genome-wide association study (GWAS) identified a common variant in ADAM10 which was associated with increased AD risk 41 , which has been confirmed in Han Chinese population 42 . These findings suggest that decreased levels and activity of ADAM10 are involved in AD pathogenesis, and ADAM10 is a promising therapeutic target 43 .…”
Section: Discussionmentioning
confidence: 94%
“…Genetic factors most likely determine the rate of disease progression (e.g., the brain-derived neurotrophic factor polymorphism) [ 19 , 20 ]. In Han Chinese, a study showed that APOE-e4, the RS2305421 GG genotype, and the RS10498633 GT genotype are associated with the Aβ plaque score, Braak neurofibrillary tangle stage, and CERAD (Consortium to Establish a Registry for Alzheimer's disease) neuritic plaque score; these results have advanced our understanding of the pathogenesis of AD [ 21 ].…”
Section: Pathogeneses and Pathological Changes In Admentioning
confidence: 99%
“…Dense-core Aβ plaques are one of the major components of AD neuropathology [ 72 ]. Importantly, the number of dense-core plaques is positively correlated with the severity of AD neuropathological changes and cognitive decline [ 73 , 74 ]. The positive correlation between the density of dense-core plaques and Braak stage in AD found in our study demonstrates that advanced dementia corresponds with high levels of AD neuropathological changes.…”
Section: Discussionmentioning
confidence: 99%